Penentuan Besaran Premi Asuransi Jiwa dengan Model Apportionable Fractional Premiums Berdasarkan Tabel Mortalita dengan Metode Interpolasi Kostaki - Muhammad Nor Abdul Rajak; Yuki Novia Nasution; Nanda Arista Rizki (EKSPONENSIAL, 2018)
Insurance is an agreement between the customer and insurance company, at which the insurance company bears some loss in the future and the customer pays the premium according to the agreement. Insurance company determines the amount of premiums based on mortality tables. The purpose of the research is to determine the characteristics of Indonesia mortaliy table with Kostaki interpolation method, to determine whole life insurance premium with apportionable fractional premiums model, and to determine the amount of the premium return. The results of the research indicate that in the mortality table of Indonesia in 2014, the number of female deaths tend to be lower than male at 1-74 years, but the number of deaths increased over the age of 75 years. The premiums paid by a 30 year-old male with a semester payment is Rp 2.358.988, quarterly payment is Rp 1.186.823, and monthly payment is Rp 397.253. The premiums paid by a 30 year-old female with a semester payment is Rp 2.044.666, quarterly payment is Rp 1.028.669, and monthly payment is Rp 344.242. Premium return of 30 years-old male is Rp 84.204.338 and of 30 years-old female is Rp 72.968.560.